Pathways of ocular entrainment in Marpissa marina (Araneae, Salticidae). Issue 4 (2nd October 2019) - Tork, Pariya
ABSTRACT: Depending on the animal species, photoreceptors are located in the visual organs, in non-visual organs or in both. Because of unique characteristics of vision containing several different pairs of eyes, I chose the jumping spider (salticid) Marpissa marina (Araneae: Salticidae; Goyen, 1892) for this study. Eyes in spiders are categorized in two groups of principal and secondary. Specifically, my aim was to determine which eyes are dedicated to regulation of the central circadian rhythm and to illuminate the pathway(s) of ocular entrainment in jumping spiders. To achieve this, I used an opaque elastic paste to prevent entry of light to the photoreceptors. My procedure was to measure spider activity levels over eight days as well as spiders responses to a 6 h delay shift in light/dark cycle. This would be made first with uncovered eyes (and sham covers) and then with distinct pairs of eyes covered. The results revealed that, unlike the secondary eyes, light information gathered through AMEs did not lead directly or indirectly to the parts of the circadian system that contain circadian pacemakers.